(3CSGSjGJ GdJMcje GdJLGQj GdOhdj h GdbhGfjf h GdGJaGbjGJ GdefXeI ddJMcje YQHjG h YGdejGs - (3eMeO(B, (3TgGHs (((3GdbGgQI(B):s (3ecJHI GdhaGA GdbGfhfjI(B,s, 2009)
(3GSGSjGJ GdJMcje GdJLGQj GdOhdj , GdGJaGbjGJ GdOhdjI GdeJUdI HGdJMcje GdJLGQj GdOhdj h Gge eQGWRg aj GdYGde , GdJMcje YHQ GdGfJQfjJ h GdefXeGJ ZjQ GdMchejI aj eLGd GdJMcje(B.s
(3edMb UhQ U(B.365s
Keywords: (3GdJMcjes; (3GdJMcje GdJLGQjs; (3GdJMcje GdOhdjs